Reforming of methane: Effects of active metals, supports, and promoters - Al-Fatesh, Ahmed S.; Patel, Naitik; Fakeeha, Anis H.; Alotibi, Mohammed F.; Alreshaidan, Salwa B.; Kumar, Rawesh (Catalysis reviews. Science and engineering, 2024)
The dry reforming reaction (DRM) had capacity to mitigate the greenhouse gases from environment as well as to produce syngas as a chemical feedstock. Various doped metal oxides, supported metal catalysts and promoted catalyst system over different supported metal catalysts had profound activity toward this specific reaction. Herein, a sequential review on DRM is presented which covers most of the excellent and conceptual work of this field from the last two decades. The review covers 8 active metals i.e. Fe, Co, Ni, Ru, Rh, Pd, Ir, Pt dispersed over 12 support system as activated carbon or Char, MgO, CeO 2 , La 2 O 3 , Y 2 O 3 , TiO 2 , Si 2 O 3 , Al 2 O 3 , ZrO 2 , SiC BN, Clay for DRM reaction. Further under each support, a deep literature review of a long range of promotors (total 35) belonging to different groups of periodic tables is elaborated. At the end, a brief about the state-of-the-art of possible industrial potent catalyst and the future research portfolio for catalytic advancement are presented.